Carbaryl Metal Chloride Complexes and Their Persistence - Arora, C.L.; Kaur, Tejinder (Asian Journal of Chemistry, 2010)
In the present note the authors described the synthesis of carbaryl-metal complexes and the role of complexation on persistence of insecticide and the deficiency of micronutrients.